Maternal residential greenness and congenital heart defects in infants: A large case-control study in Southern China. (September 2020) - Nie, Zhiqiang; Yang, Boyi; Ou, Yanqiu; Bloom, Michael S.; Han, Fengzhen; Qu, Yanji; Nasca, Philip; Matale, Rosemary; Mai, Jinzhuang; Wu, Yong; Gao, Xiangmin; Guo, Yuming; et al.
Graphical abstract: Highlights: This is the first study of congenital heart defect (CHD) association with greenness. A total of 8042 cases and 6887 controls were included. Higher levels of maternal greenness exposure were associated with lower odds of CHD. We identified a protective threshold of over 0.21 satellite-derived normalized difference vegetation index on CHD. Abstract: Background: Proximity to greenness has shown protective effects on coronary heart diseases by limiting exposure to environmental hazards, encouraging physical activity, and reducing mental stress. However, no studies have previously evaluated the impacts of greenness on congenital heart defects (CHDs). We examined the association between maternal residential greenness and the risks of CHDs. Methods: We conducted a case-control study (8042 children with major CHDs and 6887 controls without malformations) in 21 cities in Southern China, 2004 – 2016. CHDs cases were diagnosed and verified by obstetrician, pediatrician, or pediatric cardiologists, within one year. We estimated maternal residential greenness using satellite-derived normalized difference vegetation index (NDVI) in zones of 500 meters (m) and 1000 m surrounding participants' residences. Logistic regression models were used to assess NDVI-CHD relationships adjusting for confounders. Results: Interquartile range NDVI increases within 500 m or 1000 m were associated with odds ratios (OR) of 0.95 (95% confidence interval (CI): 0.92, 0.98) and 0.94 (95%CI: 0.91, 0.97) for total CHDs respectively. Air pollutants mediated 52.1% of the association. We also identified a protective threshold at 0.21 NDVI on CHD. Similar protective effects from greenness were found in most CHDs subtypes. The protective associations were stronger for fall, urban or permanent residents, higher household income maternal age ≤35 years of age, and high maternal education (ORs: ranged from 0.85 to 0.96). Conclusion: Our findings suggest a beneficial effect of maternal residential greenness on CHDs. Further studies are needed to confirm our findings, which will help to refine preventive health and urban design strategies.